Effect of sevoflurane on CD4+CD25+FOXP3+ regulatory T cells in patients with gastric cancer undergoing radical surgery: Sevoflurane’s impact on regulatory T cells in gastric cancer - Yong, Fangfang; Wang, Hemei; Li, Chao; Liu, Wei; Wang, Zhijiao; Jia, Huiqun (Cellular and Molecular Biology, 2023)
In this study, the proportion of CD4+CD25+FOXP3+ regulatory T (Treg) cells in CD4+ T cells in the peripheral blood of gastric cancer patients before anesthesia induction (T1), after surgery (T2) and the first day after surgery (T3) was studied to explore the effect of sevoflurane and propofol anesthesia on the prognosis of gastric cancer patients. Forty patients with advanced gastric cancer were recruited and randomly divided into the sevoflurane group (S group) and the propofol group (T group). Flow cytometry was used to detect the proportion of CD4+CD25+FOXP3+ Treg cells in CD4+ T cells in the peripheral blood of patients with T1, T2 and T3, respectively. Compared with stage ⅡB, the proportion of CD4+CD25+FOXP3+ Treg cells in T1, T2 and T3 of stage ⅢA and stage ⅢB patients was increased. Compared with the T group, the expression of CD4+CD25+FOXP3+ Treg cells in the peripheral blood of T2 and T3 in the S group was decreased. The results showed that the expression of CD4+CD25+FOXP3+ Treg cells might be related to the TNM stage of gastric cancer and sevoflurane could alleviate the inhibition of postoperative immune function more than propofol. Sevoflurane effectively reduced the expression level of CD4+CD25+FOXP3+ Treg cells in peripheral blood of T2 and T3 of patients with gastric cancer, providing the theoretical basis for the selection of surgical anesthetics for patients with gastric cancer.